Reduction in tuberculosis incidence in the UK from 2011 to 2015: a population-based study. Issue 8 (19th April 2018) - Thomas, H Lucy; Harris, Ross J; Muzyamba, Morris C; Davidson, Jennifer A; Lalor, Maeve K; Campbell, Colin N J; Anderson, Sarah R; Zenner, Dominik
Abstract : Background: Following nearly two decades of increasing tuberculosis in the UK, TB incidence decreased by 32% from 2011 to 2015. Explaining this reduction is crucial to informing ongoing TB control efforts. Methods: We stratified TB cases notified in the UK and TB cases averted in the UK through pre-entry screening (PES) between 2011 and 2015 by country of birth and time since arrival. We used population estimates and migration data to establish denominators, and calculated incidence rate ratios (IRRs) between 2011 and 2015. We calculated the contribution of changing migrant population sizes, PES and changes in TB rates to the reduction in TB notifications. Results: TB IRRs fell in all non-EU migrant and UK-born populations between 2011 and 2015 (0.61; 95%  CI 0.59 to 0.64 and 0.78; 0.73 to 0.83 respectively), with the greatest decrease in recent non-EU migrants (0.54; 0.48 to 0.61). 61.9% of the reduction in TB notifications was attributable to decreases in TB rates, 33.4% to a fall in the number of recent/mid-term non-EU migrants and 11.4% to PES. A small increase in notifications in EU-born migrants offset the reduction by 6.6%. Conclusions: Large decreases in TB rates in almost all populations accounted for the majority of the reduction in TB notifications, providing evidence of the impact of recent interventions to improve UK TB control. The particularly large decrease in TB rates in recent non-EU migrants provides evidence of the effectiveness of screening interventions that target this population. These findings will inform ongoing improvements to TB control.